Use of Radiation Therapy in Metastatic Nasopharyngeal Cancer Improves Survival: A SEER Analysis - Jiyi Hu (Nature Portfolio, 2017)
Abstract Limited data indicated radiotherapy might provide survival benefits to patients with distantly metastatic nasopharyngeal carcinoma (mNPC). We used the Surveillance Epidemiology and End Results database to examine the role of radiotherapy in the treatment of mNPC. Patients with mNPC at presentation diagnosed between 1988 and 2012 were enrolled. The outcome of interest included overall survival (OS) and cancer-specific survival (CSS). A total of 679 patients with a median follow-up of 13 months were identified. Four hundred forty-eight patients received radiotherapy and 231 did not. Radiotherapy was associated with significantly improved OS and CSS in both univariate and multivariate analyses. Weighted Cox regression by inverse probability of treatment weighting (IPTW) using propensity score (PS) showed a 50% reduced risk of mortality in patients who received radiotherapy with regards to both OS (HR: 0.50, 95% CI: 0.41–0.60, p < 0.001) and CSS (HR: 0.50, 95% CI: 0.40–0.61, p < 0.001), respectively. Further, patients with a younger age (<65 year-old), diagnosed after 2003, with non-keratinizing carcinoma or undifferentiated carcinoma, and who received surgery had better outcomes for both OS and CSS. Local radiotherapy was associated with improved survival in patients with mNPC. Our findings warrant prospective investigation in clinical trials.